Central schemes for ideal magnetohydrodynamics - Touma, Rony (2007)
We present second‐order accurate central finite volume methods adapted to three‐dimensional ideal magnetohydrodynamics problems. These methods alternate between two staggered grids, thus leading to Riemann solver‐free algorithms with relatively favorable computing times. The div·B = 0 constraint on the magnetic field is enforced with a suitable adaptation of the constrained transport method to our central schemes. Numerical experiments show the feasibility of the proposed methods and our results are in good agreement with existing results in the recent literature. (© 2008 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)